CLONING OF PHYTASE - PHYL GENE ISOLATED FROM BACILLUS LICHENIFORMIS (ATCC14580) INTO E.COLI DH5Α HOST - HAMZAH ABDULRAHMAN SALMAN; SELVAM ARJUNAN; RADHAKRISHNAN SENTHILKUMAR (International Journal of Pharma and Bio Sciences, 2014)
Since the mono gastric animals are not capable of metabolizing phytate, a rich source of Phosphorus, undigested phytate is excreted in manure without absorbed for metabolism and poses serious phosphorus pollution in the environment. Therefore, supplementation of phytases into animal feed is expected to solve the above problems. The present investigation deals with cloning and expression of a phytase-PhyL gene from Bacillus licheniformisin in E. coli strain DH5 alpha to facilitate large scale production of this enzyme. DNA was isolated from Bacillus licheniformis ATCC14580 and the phytase-PhyL gene was amplified. The amplified gene was cloned in ready to ligate cloning vector and cloning was confirmed by colony PCR and plasmid digestion. The reported and confirmed clone in this study will be useful in resolving the possible extensive production of recombinant phytases by means of fermentation. This cost effective phytases can be utilized as a feed supplement in animals.